(untitled) (Journal of Consumer Sciences, 2018)
The raising of competition between business holders causes various cases of losses that experienced by consumers. Therefore, the consumer independence and consumerism should be built up to prevent losses due to the crime of business holders. This study aims to analyze the factors that influence consumer independence in Generation Y. This research is using an online survey with 291 respondents. More than half of the respondents in this research were in the medium category of consumer independence, and were in the low category of consumerism. The results of this research showed that independent self-construals had a significant positive effect toward consumer independence and consumer rights awareness had a significant positive effect toward consumer independence and consumerism.